Study of Biochemical parameters and Body Mass Index along with its associated risk factors among Health Science students- A cross-sectional study - Shreevastva, Naveen Kumar; Makaju, Hari Sharan; Dhungana, Arun; Pandeya, Arun (Birat Journal of Health Sciences, 2020)
Introduction: Body mass indexis a valuable tool used to identify disorders caused by nutritional imbalance, either undernutrition or overnutrition. Neither underweight nor overweight and obesity is a desirable health status and may cause negative health outcomes. Objectives: The aim of this study was to determine body mass index among medical,dental and nursing students and to assess the factors associated with it. Methodology: This cross-sectional study was conducted in health science students of Kathmandu Medical College Public Limited, Kathmandu, NepalfromMay 2017 to July 2018. Body Mass Index (BMI) was calculated in 644 students including both male and female of Medical, Dental and Nursing students. Blood samples were collected from the students having BMI > 24.9Kg/m2for the estimation of triglyceride, cholesterol and glucose which were compared with the same parameters of students whose BMI was normal (≤24.9 Kg/m2). Results: A Total of 644 study population was taken, the majority ranges between 17-20 years. The occurrence of overweight was higher in the male (10.1%) of medical and in the female (8.4%) of dental students. The prevalence of overweight and obesity among the study group was found to be 8.7% and 2.8% respectively.Serum triglyceride, cholesteroland glucose concentrations in the subject with BMI > 24.9Kg/m2were significantly higher than that in subject with BMI ≤24.9 Kg/m2. Conclusion: Obesity and overweight are prevalent among the students. As a result, the biochemical parameters such as triglycerides, glucose and cholesterol show significantly higher values.